2019
DOI: 10.1016/j.aott.2019.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Revision strategy for malunited tibial plateau fracture caused by failure of initial treatment

Abstract: ObjectiveThe aim of this study was to evaluate our treatment algorithm and results in revision surgery of malunited tibial plateau fracture after failure of initial treatment.MethodsOur revision strategy was as follows: First, we determined the presence of any infection. Second, we determined whether the patient required total knee arthroplasty (TKA). Third, based on the characteristics of the tibial plateau fracture malunion, patients underwent one of the following surgical methods to achieve reduction: origi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 21 publications
2
14
0
Order By: Relevance
“…They showed that a correction of the intraarticular depression and valgus malalignment provides good results and that the anatomic leg axis was restored in all patients. In line with Krettek et al and Liangjun et al, we believe that a malunited TPF is better treated with intraarticular osteotomy to gain an anatomical articular surface and alignment restoration [ 5 , 20 ]. Liangjun et al analysed 25 patients with malunited TPF while in 15 cases an intraarticular osteotomy was performed and satisfactory patient outcomes were achieved [ 5 ].…”
Section: Discussionsupporting
confidence: 66%
See 3 more Smart Citations
“…They showed that a correction of the intraarticular depression and valgus malalignment provides good results and that the anatomic leg axis was restored in all patients. In line with Krettek et al and Liangjun et al, we believe that a malunited TPF is better treated with intraarticular osteotomy to gain an anatomical articular surface and alignment restoration [ 5 , 20 ]. Liangjun et al analysed 25 patients with malunited TPF while in 15 cases an intraarticular osteotomy was performed and satisfactory patient outcomes were achieved [ 5 ].…”
Section: Discussionsupporting
confidence: 66%
“…In line with Krettek et al and Liangjun et al, we believe that a malunited TPF is better treated with intraarticular osteotomy to gain an anatomical articular surface and alignment restoration [ 5 , 20 ]. Liangjun et al analysed 25 patients with malunited TPF while in 15 cases an intraarticular osteotomy was performed and satisfactory patient outcomes were achieved [ 5 ]. Wang et al demonstrated 13 patients with posterolateral tibial plateau fracture malunion and intraarticular osteotomy at a mean follow-up of 20 months [ 6 ].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…In current practice, routine use of the computer tomography (CT) scan led to the development of multiple CT-based classi cations, which has made it possible to identify the coronal plane fracture and localize the fracture with respect to the quadrants [2,3]. Yet, it is not very infrequent to encounter signi cant malunion after surgical management of split and depression lateral tibial plateau fracture, which mandates revision surgery or conversion to the arthroplasty [4,5]. Meulenkemp et al [6] also reported that the lateral tibial plateau is the commonest area to encounter malunion and incidence may range 23 to 77%.…”
Section: Introductionmentioning
confidence: 99%